An overview and history of leadership and leadership development - Burgoyne, John (Henry Stewart Talks, 2010)
History of leadership, Leadership theory, Leadership development, Leadership: A contemporary review, Law of the situation, Leaders as followers, Organisational learning
Updated at 2016/09/28